ANALISIS PENGARUH PELAYANAN TERHADAP CUSTOMER RETENTION PADA PT. BANK MUAMALAT INDONESIA KC BALAIKOTA MEDAN - Khairun Nisa; Mustapa Khamal Rokan; Mawaddah Irham (Jihbiz: Global Journal of Islamic Banking and Finance., 2022)
Service quality is a measure of how well the level of service performance provided by a company compare to customer expectations. Service quality determines whether the perceived service delivery meets, exceeds, or fails to meet customer expectations. Service quality is very important for the sustainability of the bank, because service is a factor that is felt directly by customers, whether the service provided is good or bad. This study aims to determine the effect of services including tangible, reliability, responsiveness, assurance and empathy on customer retention. The method used in this research is quantitative research with associative approach. Data analysis technique used in this research is descriptive test, validity test, reliability test, classical assumption test, multiple linear regression test and hypothesis testing through ttest and Ftest as well as coefficient of determination test. Testing is done by using SPSS. The results showed that the variables in this study are valid and reliable. The classical assumption test, the data is normally distributed, there is no heteroscedasticity and multicollinearity. The results of the hypothesis test (t test) found that tangible and reliability do not have a significant effect to customer retention. While responsiveness, assurance and empathy have a positive and significant effect to customer retention. So it can be concluded that the variable tangible, reliability, responsiveness, assurance and empathy simultaneously have a significant effect to customer retention. It also can be seen from the results of the coefficient of determination test (r2), it shows that the magnitude of variable tangible, reliability, responsiveness, assurance and empathy is 70.4% on customer retention, the remaining 29.6% is influenced by other variable outside the research that are not examined in this study such as product quality, trust, commitment, promotion and others.